Implementation of Robotics Process Automation (RPA) and its impact on unemployment in South Africa - Ngubevana, Atenkosi (My University, 2018)
The concept of automation is one that can be traced back to primitive man and the notion of humans being displaced from one industry to another is not a new phenomenon. If our evolutionary history is anything to go by, we as humans have little to concern ourselves about with the introduction of new technologies like RPA. This research focused primarily on defining what RPA is and establishing if its implementation will have an impact on the South African unemployment levels. The research further looked at the roles that have a high degree of automation and the new roles that have been and will be created by the implementation of RPA. The research did not focus on companies but its main focus was to highlight the vast industries that RPA is being implemented in, thus depicting the possible reach of its impact. The data was collected through a series of face-to-face semi-structured interviews with different individuals who have participated in the implementation of RPA. The interview findings were summarised, contrasted and compared to literature. The main themes that arose out of the research included the unified definition and understanding of RPA is which was greatly supported by literature. The research further highlighted the ability for RPA to de-risk multiple back office processes that are currently processed by humans. The pace of automation was also discussed in detail, where the research findings concluded that the pace of automation is greatly influenced by the complexity of the process and the number of systems that are involved. One of the key findings of the research is that history is not a great indicator of future events. Previous waves of automation occurred over prolonged periods and affected a few industries and firms at a time. This type and rapid pace of automation is one that cannot be ignorantly be grouped, as its impacts may have a largely negative influence on employment levels in South Africa.
MBA
Keywords: Business -- Automation. Automation. Industries -- Automation.